The sharing economy in a post-Covid-19 world: Insights from Islamic economic history - Jamila Abubakar; Nasim Shah Shirazi (Review of Islamic Social Finance and Entrepreneurship, 2023)
Purpose – The Covid-19 and climate change crises have increased attention to building a more circular global economy. This paper analyses the insufficiency of the linear economy growth model in a post-Covid-19 world and sheds light on the role of the sharing/collaborative economy in the post-Covid-19 socio-economic recovery.Methodology – An explanatory approach is employed to broaden the theoretical idea of the Sharing Economy (SE) as a contemporary concept by delving into the historical applications and motivations of sharing and collaborative practices in the Islamic economy and hunter-gather societies.Findings – Although contemporary sharing economy platforms are credited with the sharing economy concept, history shows that pre-modern societies have used sharing concepts to maximize efficiency in allocating resources, and collaborative consumption predates the digital economy. The paper also finds that adopting Islamic economy ideologies for social solidarity could address contemporary sharing economy models' challenges.Implications – The paper fills a gap in the literature by learning from historical sharing practices and adopting Islamic economy ideologies for social solidarity; the sharing economy could contribute significantly to building a circular global economy.Originality – By delving into the historical applications and motivations of sharing and collaborative practices in the Islamic economy and hunter-gatherer societies, this paper brings a unique perspective that is rarely studied.